Pedagogical Latency and Disciplinary Friction: An Archival Analysis of How Global Volatility Impacts Cambridge A-Level Economics and Business Curricula (2004–2028) - Maliha Abdul Mujeeb; Dr. Muhammad Yousuf Sharjeel; Dr. Nuzhat Naz (Journal for Social Science Archives, 2025)
The past two decades have subjected the global economy to unprecedented volatility, fundamentally challenging the orthodox models taught in international secondary education. This study conducts a longitudinal qualitative archival document analysis of the Cambridge Assessment International Education (CAIE) A-Level frameworks between 2004 and 2028 to investigate how macroeconomic trauma dictates curriculum evolution. By comparatively tracking a theoretical discipline (Economics 9708) and an applied discipline (Business 9609/9707), this research empirically identifies severe "disciplinary friction." Findings reveal that theoretical economics functions as a "reactive historical archivist," exhibiting profound pedagogical latency—evidenced by a five-year delay in codifying Quantitative Easing post-2008 and a decades-long resistance to Behavioral Economics—adapting only to preserve academic orthodoxy. Conversely, applied business operates as a "proactive educational agent," rapidly restructuring its syllabus to integrate Corporate Social Responsibility (CSR) and global strategic resilience in response to the modern "Age of Disruption." The study concludes that standard, rigid syllabus update cycles are insufficient for modern geopolitical volatility. It recommends the adoption of modular curriculum frameworks, the integration of heterodox economic theories, and targeted experiential learning mandates to close the persistent theory-practice gap and equip students for future systemic crises.